“Evaluación de las competencias lingüísticas en los niños de tercer año de educación general básica de la Unidad Educativa Abdón Calderón” - Rosero Limones, Blanca Alexandra (2023)
The present project assumes as a general objective to evaluate the level of linguistic competences (at the level of mastery of oral language and mastery of metalinguistic skills) in the children of the Third Year of Basic General Education of the Abdón Calderón Educational Unit. For this, a quantitative approach was carried out in order to measure the study variable, in addition, a cross-sectional descriptive scope was applied where it was sought to describe, in a single moment in time and through the application of an instrument, the linguistic competences present. in a group of children from the Educational Institution. In the same way, a non-experimental design was carried out since the variable was not manipulated. Based on the population and sample, it consisted of 42 students, of whom 20 were boys and 22 girls. The technique used was the survey and the instrument applied was the Child Neuropsychological Evaluation Test (ENI) by Rosselli (2007). According to the results obtained, 35.71% of the girls reached an average command of oral language (26 - 75), while 11.90% of the boys showed a low average (11 - 25). Likewise, when applying the test in the metalinguistic skills domain, 23.81% of the male gender reached an average level, as did 26.19% of the girls. Finally, it is concluded that the linguistic competences of boys represent 47.61% and that of girls 52.37%, which means that they do not present so many complications in terms of the development of linguistic competences.